SCIENTIFIC AND THEORETICAL BASES OF THE MANAGEMENT OF INVERTING IN DEVELOPMENT PROJECTS - J. Antokhina; A. Kolesnikov; S. Kornilova (Вестник Северо-Кавказского федерального университета, 2022)
The article discusses the full range of scientific and theoretical foundations for the management of significant development projects (SDP), taking into account both their economic and institutional features. The features of scientific approaches to the management of investments in SDPare revealed. The institutional aspect in the ield of investment in development projects is considered, the features of scientiic approaches to investment management in SDP with its account are revealed.